2021
DOI: 10.17718/tojde.906816
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Classroom Management and Sense of Classroom Community in Graduate Virtual Classrooms

Abstract: Communication, motivation, time management, rules and behavior management, plan program activities and physical order are important in the management of virtual classrooms, as they are in the management of traditional classrooms. On the other hand, "sense of classroom community" in online learning environment is classified with connectedness and learning dimensions. Hence, both constructs are crucial for virtual classrooms, the aim of the study was to examine the relationship between classroom management and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“…Pengelolaan kelas dengan baik akan memberikan interaksi belajar mengajar yang baik pula (Kavrayici, 2021;Mansor, Eng, Rasul, Mohd Hamzah, & Hamid, 2012;Wolff, Jarodzka, & Boshuizen, 2021). Tujuan pembelajaran juga dapat dicapai tanpa menemukan hambatan yang berarti.…”
Section: Pendahuluan Berdasarkanunclassified
“…Pengelolaan kelas dengan baik akan memberikan interaksi belajar mengajar yang baik pula (Kavrayici, 2021;Mansor, Eng, Rasul, Mohd Hamzah, & Hamid, 2012;Wolff, Jarodzka, & Boshuizen, 2021). Tujuan pembelajaran juga dapat dicapai tanpa menemukan hambatan yang berarti.…”
Section: Pendahuluan Berdasarkanunclassified
“…Algahtani [10] reported that poor infrastructure and a lack of acceptance of e-learning were perceived by the e-learners as barriers to effective learning. Kavrayici [11] found that implementation dimensions of classroom management, and leadership and instructional planning positively predicted the connectedness dimension of classroom community.…”
Section: E-learningmentioning
confidence: 99%
“…Classroom management practices play a fundamental role in shaping the learning environment and impacting student motivation (Berger et al, 2018). A wellmanaged classroom provides structure, consistency, and clear expectations, creating a conducive space for learning and growth (Kavrayıcı, 2021). Positive classroom management strategies, such as establishing routines, implementing fair and consistent discipline policies, and promoting a positive teacher-student relationship, can positively influence student motivation (Muhammad et al, 2023).…”
Section: Introductionmentioning
confidence: 99%